How much expectation and how much satisfaction do the studies of Economic Engineering and Statistics at UNI provide? - Quiroz Vera, Eduardo Fernando (2015)
Within the framework of the research activities promoted by IECOS, this project was carried out in 2015 and we present a summary of the results achieved. For the selection of FIEECS graduates, a non-probabilistic sampling of intentionality or opinionated sampling was used (because the FIEECS does not have a complete record of the graduates currently working). The technique used was the survey. For the analysis of the data obtained, statistics such as frequency distribution, graphs and Chi-square test were used.